2019
DOI: 10.1111/asj.13302
|View full text |Cite
|
Sign up to set email alerts
|

Presence of chlorogenic acid during in vitro maturation protects porcine oocytes from the negative effects of heat stress

Abstract: Chlorogenic acid (CGA) is known to protect oocytes from oxidative stress. Here we investigated the effects of CGA on porcine oocyte maturation under heat stress and subsequent embryonic development after parthenogenetic activation. For in vitro maturation (IVM) at 41.0°C (hyperthermic condition), supplementation of the maturation medium with 50 μM CGA significantly improved the percentage of matured oocytes and reduced the rate of apoptosis relative to oocytes matured without CGA (p < .05). CGA treatment of oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…A protective effect of CGA on DNA integrity as well as on MMP was observed. These results are supported by the observation that CGA protected in vitro porcine oocytes from the negative effects of heat stress and from DNA damage [ 44 ]. In addition, since mitochondria generate energy to support motility, high percentage of sperm with high MMP represents an index of cellular activity, vitality, and integrity of mitochondrial cristae.…”
Section: Discussionmentioning
confidence: 53%
“…A protective effect of CGA on DNA integrity as well as on MMP was observed. These results are supported by the observation that CGA protected in vitro porcine oocytes from the negative effects of heat stress and from DNA damage [ 44 ]. In addition, since mitochondria generate energy to support motility, high percentage of sperm with high MMP represents an index of cellular activity, vitality, and integrity of mitochondrial cristae.…”
Section: Discussionmentioning
confidence: 53%
“…However, there were no differences in nuclear maturation and the proportion of oocytes with fragmented DNA between the antioxidant‐supplemented and control groups. In contrast, other studies have shown that supplementation with curcumin (Namula et al., 2020) and CGA (Nguyen et al., 2019) during maturation in the absence of cysteine increased nuclear maturation and protected oocytes from DNA fragmentation. The lack of positive effect of antioxidants supplementation on nuclear maturation and DNA damage in the oocytes may be partly due to adding 0.6 mM cysteine during maturation culture.…”
Section: Discussionmentioning
confidence: 76%
“…Chlorogenic acid (CGA) is a phenolic acid found mainly in coffee. CGA plays an essential role in protecting porcine oocytes from oxidative stress induced by heat stress and electroporation (Nguyen et al., 2018,2019). Our earlier study had demonstrated that application of 50 μM CGA improved maturation rates, fertilization and blastocyst formation and reduced the percentage of DNA fragmentation in porcine oocytes exposed to oxidative stress induced by H 2 O 2 during maturation culture (Nguyen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“… Namula et al (2018) suggested that CA supplementation improved certain sperm parameters, including viability, plasma membrane integrity, and motility, during boar sperm freezing. Nguyen et al (2019) found that CA supplementation during in vitro maturation could protect porcine oocytes from DNA damage induced by oxidative stress and improve their subsequent developmental competence after fertilization.…”
Section: Introductionmentioning
confidence: 99%